The choice of the enterprise development strategy in the context of the economic crisis - Kabdulsharipova, А.М.; Suieubayeva, S.N.; Madiyarova, E.S.; Ozpence, O. (BUKETOV BUSINESS REVIEW, 2018)
Timely and informed choice of the development strategy is extremely important for business in crisis, fierce competition and a quickly changing situation. When choosing a development strategy must consider not only factors external and internal environment, but also the concept of strategic management. It's necessary to use such a method of choosing a strategy that would take into account the calculation of the criteria can be qualitative. These aspects cover different stages of the strategic process. In this article we propose a refined model of the choice of strategy of development of the enterprise, which enables industrial companies to select the most promising development strategy in the context of the global crisis, taking into account all relevant factors. The proposed method is to select the priority of the development strategy of the company through the method of PARK (steam compensation) of two strategies selected separately for conditionally-objective and quasi-subjective approaches, to account for these factors and reduce the error rate of wrong choice of strategy. The algorithm of development strategy is presented which shows that one important task of enterprise management is to increase the efficiency of complex development, which includes a high degree of reactivity to market changes or other circumstances, and the provision of new or upgraded services or products.